Study of the Effect of Treatment With Atrial Natriuretic Peptide (ANP) and Cinaciguat in Chronic Hypoxic Neonatal Lambs on Residual Strain and Microstructure of the Arteries - Navarrete, Alvaro; Chen, Zhuoming; Aranda, Pedro; Poblete, Daniel; Utrera, Andrés; García-Herrera, Claudio M.; Gonzalez-Candia, Alejandro; Beñaldo, Felipe A.; Ebensperger, German; Reyes, Roberto V.; Herrera, Emilio A.; Llanos, Anibal J. (Frontiers in Bioengineering and Biotechnology, 2020)
In this study, we assessed the effects of Atrial Natriuretic Peptide (ANP) and Cinaciguat, as experimental medicines to treat neonatal lambs exposed to chronic hypoxic conditions. To compare the different treatments, the mechanical responses of aorta, carotid, and femoral arterial walls were analyzed by means of axial pre-stretch and ring-opening tests, through a study with n=6 animals for each group analyzed. The axial pre-stretch test measures the level of shortening in different zones of the arteries when extracted from lambs, while the ring-opening test is used to quantify the degree of residual circumferential deformation in a given zone of an artery. In addition, histological studies were carried out to measure elastin, collagen, and smooth muscle cell nuclei densities, both in control and treated groups. The results show that mechanical response is related with histological results, specifically in the proximal abdominal aorta (P.A.A.) and distal carotid zones (D.C.A.), where the cell nuclei content is related to a decrease of residual deformations. The opening angle and the elastic fibers of the aorta artery were statistically correlated (p<0.05). Specifically, in P.A.A. zone, there are significant differences of opening angle and cell nuclei density values between control and treated groups (p-values to opening angle: Control-ANP=2∙10-2, Control-Cinaciguat=1∙10-2; p-values to cell nuclei density: Control-ANP=5∙10-4, Control-Cinaciguat=2∙10-2). Respect to distal carotid zone (D.C.A.), significant differences between Control and Cinaciguat groups were observed to opening angle (p-value 4∙10-2), and cell nuclei density (p-value=1∙10-2). Our findings add evidence that medical treatments may have effects on the mechanical responses of arterial walls and should be taken into account when evaluating the complete medical outcome.